Preparation of a purified antigenic cholera toxoid. - Germanier, R (1976)
Purified cholera enterotoxin was prepared by methods described by Finkelstein and Lo Spalluto (1970). This toxin was detoxified by treatment with heat and formaldehyde. Heating cholera toxin at 60 C for 25 min resulted in the formation of a polymer named procholeragenoid by Finkelstein et al. (1971). The weak toxic activity of this product was removed by treatment with formalin. No residual toxicity could be demonstrated in formalinized procholeragenoid by the rabbit ileal loop assay and the highly sensitive rabbit skin tests. This toxoid was nevertheless at least as antigenic in the rabbit as was the toxin. No reversion to toxicity was observed in vivo and in vitro at 4 C. The toxicity of formalinized procholeragenoid never exceeded 1/5,000 to 1/10,000 that of the toxin.